Management of the Free Nutritious Meal Program in Elementary Schools: A Qualitative Study of Teacher Practices in Bengkulu City, Indonesia - Nova Asvio; Dela Puspita Sari; Meli Astuti; Heny Friantary (PPSDP International Journal of Education, 2026)
This study examines the management of Indonesia’s Free Nutritious Meal (MBG) program at the classroom level, focusing on planning, organizing, implementation, and evaluation by second-grade teachers at SD Negeri 66, Bengkulu City. A qualitative descriptive design was employed, with data collected through observation, semi-structured interviews (n=8: 1 teacher, 1 principal, 6 students), and documentation over one semester. Data were analyzed using Miles and Huberman’s interactive model. Findings reveal that MBG management remains largely informal and operational. Planning focuses on improving student nutrition and reducing breakfast skipping through coordination with food providers and nutritionists. Organizing involves teachers and students with flexible, spontaneous task division. Implementation proceeds through teacher-student collaboration in food distribution, adapted to provider arrival schedules. Evaluation is conducted through simple observation of student enthusiasm and food quality, with feedback provided to providers for improvement. While the program supports students’ nutritional needs and demonstrates high student engagement, challenges persist in structured coordination, systematic documentation, and food quality control. This study contributes empirical evidence on frontline implementation of school feeding programs in Indonesia and recommends more systematic, documented management approaches at the school level.